(untitled) (Biological Sciences - PJSIR, 2003)
Separation of mixture of isomeric organic compound was achieved by exploiting the difference in their dissociation constants by employing dissociation extraction technique. Mixture of 3-picoline and 4-picoline was partially separated with sodium dihydrogen phosphate to demonstrate the phenomenon of dissociation extraction. A theoretical treatment of separation of isomers is given which can be utilized to predict the separation factor of dissociated and undissociated species of isomers. Increase in temperature had a positive influence on the separation of isomers and also on the phase disengagement between the aqueous and the organic phases. A process is described to develop a suitable chemical material bed in the column for gas-liquid chromatograph that reduces the retention time and gives high resolution of picolines.